PENGARUH PENGEMBANGAN KARIER TERHADAP KINERJA PEGAWAI PT PLN UPT SULSELRABAR - Aam Azatil Isma; Otto Randa Payangan; Dian Anggraece Sigit Parawansa (Jurnal Ilmiah Administrasita', 2020)
Career development is a necessity which should continue to be developed within an employee so that it is able to motivate employees to improve performance. This study aims to determine and analyze the influence of career development on employee performance. Data were analyzed by PLS method. Results of the analysis showed that the career development testing positive and significant impact on performance, so that the research hypothesis is accepted.